Funcionalidade e incapacidade no cuidado fisioterapêutico após Acidente Vascular Cerebral: uma revisão de escopo - Vieira, Sofia Queiros (2024)
The impacts of stroke place a heavy burden on stroke survivors, their caregivers and the health and socio-economic sectors. In the field of rehabilitation, the use of the biopsychosocial model guarantees more comprehensive care and using functioning and disability indices indicates the needs of the population more accurately. Physiotherapists have been working on functioning/disability outcomes in people who have suffered a stroke, but there is no information on how the approach is taken from the perspective of the biopsychosocial model. This dissertation aimed to study the approach to functioning/disability, from a biopsychosocial perspective, in the post-stroke care offered by physiotherapy in different intervention settings. A scoping review was conducted to investigate clinical trials that included functioning or disability as an outcome, and that compared one physiotherapeutic intervention to another or no intervention in adults who after stroke. The search was carried out in 8 databases (Medline, PEDro, Embase, Scopus, LILACS, CINAHL, Web of Science and Cochrane CENTRAL database). Two independent reviewers analyzed 5554 articles in a two-stage screening that ended in 25 articles. The outcomes and their assessment instruments were extracted, as well the intervention setting of each study. Two blinded reviewers linked the concepts of the instruments to the International Classification of Functioning, Disability and Health (ICF). Coding allowed for a detailed content analysis to compare the approaches between the intervention settings. For both outcomes, the activity categories were the most covered and there was little coverage of participation and environmental factors. The hospital setting had the greatest coverage of the ICF. The results of this study can help professionals examine their clinical practice in order to adapt the choice of assessment measures and intervention elements to make care more comprehensive. The data also provides initial information for managers to use the biopsychosocial model and functioning and disability indices to plan and organize post-stroke rehabilitation sectors.